Effects of Processing on Nutritional and Sensory Qualities of Beef Burgers Incorporated With Palm Fats - Wan Rosli, W. I.; Babji, A.S.; Aminah, A.; Foo, S. P.; Abd Malik, O. (Persatuan Pemakanan Malaysia, 2005)
A study was undertaken to investigate the effects of processing on the nutritional and sensory qualities of beef burgers formulated with palm fats as animal fat analogues. After processing, a-tocopherol and a-tocotrienol levels were significantly decreased, ranging from 46-48% to 36-44% respectively, in beef burgers made with red palm fat (RPF35) and fat blend. The changes in the levels of g-tocotrienol and d-tocotrienol after processing in all beef burgers except for the control were not statistically significant (P>0.05). After processing, a-carotene and b-carotene levels were significantly decreased, ranging from 27-40% to 42-54% in beef burgers formulated with fat blend and RPF35. After cooking, a-tocopherol and a-tocotrienol in all cooked beef burgers, except the control, were significantly decreased with levels ranging from 18- 50% to 17-46% respectively. The changes in the levels of a-carotene and b- carotene after cooking were also statistically significant (36-47% and 48-62% loss, respectively). Substitution of animal fats with palm-based fats reduced the content of cholesterol in beef burgers. The taste panel was not able to differentiate the sensory attributes such as colour, juiciness and oiliness of beef burgers formulated with palm-based fats and beef fat. Overall levels of carotene and vitamin E were higher in palm fat burgers but losses occurred upon processing and cooking.